2007
DOI: 10.1017/s0305004107000151
|View full text |Cite
|
Sign up to set email alerts
|

Total curvature, ropelength and crossing number of thick knots

Abstract: We first study the minimum total curvature of a knot when it is embedded on the cubic lattice. Let $\mathcal{K}$ be a knot or link with a lattice embedding of minimum total curvature $\tau(\mathcal{K})$ among all possible lattice embeddings of $\mathcal{K}$. We show that there exist positive constants c1 and c2 such that $c_1\sqrt{Cr(\mathcal{K})}\le \tau(\mathcal{K})\le c_2 Cr(\mathcal{K})$ for any knot type $\mathcal{K}$. Furthermore we show that the powers of $Cr(\mathcal{K})$ in the above inequalities are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…To find the exact values of the lattice stick number of these knots, they used a lower bound on lattice stick number in terms of bridge number, s L (K) 6b(K), which was proved in [10]. Furthermore Diao and Ernst [3] found a general lower bound in terms of the crossing number c(K), which is s L (K) 3 √ c(K) + 1 + 3 for a non-trivial knot K. Recently Hong et al [5] found a general upper bound s L (K) 3c(K) + 2, and moreover s L (K) 3c(K) − 4 for a non-alternating prime knot.…”
Section: Introductionmentioning
confidence: 99%
“…To find the exact values of the lattice stick number of these knots, they used a lower bound on lattice stick number in terms of bridge number, s L (K) 6b(K), which was proved in [10]. Furthermore Diao and Ernst [3] found a general lower bound in terms of the crossing number c(K), which is s L (K) 3 √ c(K) + 1 + 3 for a non-trivial knot K. Recently Hong et al [5] found a general upper bound s L (K) 3c(K) + 2, and moreover s L (K) 3c(K) − 4 for a non-alternating prime knot.…”
Section: Introductionmentioning
confidence: 99%
“…Each component contains at least two x-sticks, two y-sticks and two z-sticks since both are nonplanar. We may say that (L) is one of (4, 4, 4), (4,4,5), (4,4,6) or (4,5,5). Now consider the projection of L onto an xy-plane.…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…To find the exact values of the lattice stick number of these knots, they used a lower bound on lattice stick number in terms of bridge number, s L (K) ≥ 6b(K), which was proved in [11]. Furthermore Diao and Ernst [4] found a general lower bound in terms of crossing number c(K) which is s L (K) ≥ 3 c(K) + 1 + 3 for a nontrivial knot K. Recently Hong, No and Oh [6] found a general upper bound s L (K) ≤ 3c(K)+2, and moreover s L (K) ≤ 3c(K) − 4 for a non-alternating prime knot.…”
Section: Introductionmentioning
confidence: 99%
“…To find the exact values of the lattice stick number of these knots, they used a lower bound on lattice stick number in terms of bridge number, s L (K) ≥ 6b(K), which was proved by Janse van Rensburg and Promislow [10]. Furthermore Diao and Ernst [4] found a general lower bound in terms of crossing number c(K) which is s L (K) ≥ 3 c(K) + 1+3 for a nontrivial knot K. Hong, No and Oh [5] found a general upper bound s L (K) ≤ 3c(K)+2, and moreover s L (K) ≤ 3c(K)−4 for a non-alternating prime knot. They [6] also showed that s L (2 2 1 ) = 8, s L (2 2 1 ♯2 2 1 ) = s L (6 3 2 ) = s L (6 3 3 ) = 12, s L (4 2 1 ) = 13, s L (5 2 1 ) = 14 and any other non-split links have stick numbers at least 15.…”
Section: Introductionmentioning
confidence: 99%